Игра: Роман / Юрий Бондарев. - Бондарев Юрий Васильевич (Мол. гвардия, 1985)
Экземпляры: ЧЗ (20160523) / Инвентарный номер: 13447 / Цена: 1.00 / Сис.шифр: Р2 / Авт.знак: Б81 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-4